2021
DOI: 10.1128/aac.01966-20
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antibacterial Activity of Hydrogen Peroxide and Hypochlorous Acid, Including That Generated by Electrochemical Scaffolds

Abstract: Hydrogen peroxide (H2O2) and hypochlorous acid (HOCl) are biocides used for cleaning and debriding chronic wound infections, which often harbor drug resistant bacteria. Here, we evaluated the in vitro activity of H2O2 and HOCl against 27 isolates of eight bacterial species involved in wound infections. Minimum inhibitory concentrations (MICs) and minimum biofilm bactericidal concentrations (MBBCs) were measured. When compared to their respective MICs, MBBCs of isolates exposed to H2O2 were 16- to 1,024-fold hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…Two devices have been developed based on an electrochemical H 2 O 2 concept: e‐scaffolds were developed to assess activity against biofilms grown in liquid growth media, and then e‐bandages were developed to treat agar membrane (and eventually wound) biofilms. e‐Scaffolds demonstrated anti‐biofilm efficacy against mono‐, dual‐ and tri‐species bacterial and fungal biofilms, without significant toxicity to host tissue in an ex vivo porcine explant model (Raval et al, 2019 , 2020 ; Raval, Flurin, et al, 2021 ; Sultana et al, 2015 , 2016 ). In addition, it was suggested that H 2 O 2 generation by the electrode was the dominant mechanism of action (Sultana et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Two devices have been developed based on an electrochemical H 2 O 2 concept: e‐scaffolds were developed to assess activity against biofilms grown in liquid growth media, and then e‐bandages were developed to treat agar membrane (and eventually wound) biofilms. e‐Scaffolds demonstrated anti‐biofilm efficacy against mono‐, dual‐ and tri‐species bacterial and fungal biofilms, without significant toxicity to host tissue in an ex vivo porcine explant model (Raval et al, 2019 , 2020 ; Raval, Flurin, et al, 2021 ; Sultana et al, 2015 , 2016 ). In addition, it was suggested that H 2 O 2 generation by the electrode was the dominant mechanism of action (Sultana et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…S2 ). Through continuous production of H 2 O 2 and based on results herein and previously described [ 20 , 46 ], it may be possible that the described e-bandage system can overwhelm some of these oxidative stress response systems.…”
Section: Discussionmentioning
confidence: 72%
“…Biofilms formed by a catalase mutant isolate of P. aeruginosa were sensitive to H 2 O 2 . In recent work, it was demonstrated that P. aeruginosa PA14 ΔkatAB had lower minimum biofilm inhibitory and minimum biofilm bactericidal concentrations compared to its wild type parent isolate P. aeruginosa PA14 [ 46 ]. Moreover, in the current work, an increase in biofilm reduction of P. aeruginosa PA14 ΔkatAB compared to its wild type parent isolate P. aeruginosa PA14 was observed when exposed to an H 2 O 2 -producing e-bandage for 24 h ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In previous work, Raval et al ( 27 ) determined the MICs of HOCl for 27 isolates, including S. aureus , S. epidermidis , E. faecium , and E. coli . The MICs for 6 S. aureus and 3 S. epidermidis isolates ranged from 990 to 1,690 μM, and the MICs for E. faecium and E. coli isolates were 990 μM HOCl; concentrations above 286 μM are cytotoxic to mammalian cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%